2018
DOI: 10.1002/ece3.4292
|View full text |Cite
|
Sign up to set email alerts
|

Advances in assessing Sabellaria spinulosa reefs for ongoing monitoring

Abstract: Standardized and repeatable data acquisition and analyses are required to enable the mapping and condition monitoring of reefs within Marine Protected Areas (MPAs). Changes in habitat condition must be reliably identified and reported to best support evidence‐based management. Biogenic reefs in temperate waters, that is, hard matter created by living organisms and raised above the seabed, provide food and shelter for many plant and animal species. This article explores the feasibility of habitat mapping, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 21 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…Notable differences in reef detail were present between the two methods (Figure 7). Out of the 116 images taken across Stations 7, 8, 1,5 and 16 in Swansea Bay during CLOC deployments, 67 identified reef structures of either ‘Low’ or ‘Medium’ (58%) and 49 recorded ‘No Reef’ (42%) based on Jenkins et al (2018) criteria. Out of the 47 images taken across these four stations during non‐CLOC deployments, one identified a reef structure of ‘Low’ (2%) and 46 recorded ‘No Reef’ (98%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notable differences in reef detail were present between the two methods (Figure 7). Out of the 116 images taken across Stations 7, 8, 1,5 and 16 in Swansea Bay during CLOC deployments, 67 identified reef structures of either ‘Low’ or ‘Medium’ (58%) and 49 recorded ‘No Reef’ (42%) based on Jenkins et al (2018) criteria. Out of the 47 images taken across these four stations during non‐CLOC deployments, one identified a reef structure of ‘Low’ (2%) and 46 recorded ‘No Reef’ (98%).…”
Section: Resultsmentioning
confidence: 99%
“…The visualization of S. alveolata reefs in images recorded using the CLOC was also greatly enhanced when compared with those collected during non‐CLOC deployments. These reefs are considered as being of high conservation importance and are protected under a range of national and international legislations (Gubbay, 2007; Jenkins et al, 2018). Biogenic reefs provide microhabitats for other organisms, leading to higher levels of biodiversity when compared with their surrounding environment (Jonsson et al, 2004; Limpenny et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the North Sea, most reefs are located near the British coast (Fariñas-Franco et al, 2014;Gibb et al, 2014;Pearce, 2014). They are often encountered on rocky substrates (Pearce, 2014), but are also observed on sandy bottoms (Pearce et al, 2014;Jenkins et al, 2018). The worms excrete fecal matter that may increase local food availability (Pearce, 2014), while the reefs increase habitat complexity and provide refugia and settlement substrate (Hendrick and Foster-Smith, 2006;Pearce et al, 2013;van der Reijden et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Classification success is defined as the number of investigators which similarly identified an organism fraction of the total number of investigators (n = 3). Jenkins et al (2018) from the elevation and percentage cover categories proposed by Gubbay (2007).…”
Section: Chaptermentioning
confidence: 99%